2016
DOI: 10.1091/mbc.e16-01-0042
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic activation of Sox2 gene in the developing vertebrate neural plate

Abstract: The in vivo requirement of the histone demethylase JmjD2A, together with the kinase MSK1, results in a series of epigenetic events necessary for early activation of Sox2 and subsequent neural fate commitment in vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Our data also suggest a high co-localization of activated STAT3 with SOX2+ cells in BCa. Another possible mechanism of Sox2 activation is epigenetic regulation; SOX2 can be activated by JMJD2A ( Bouzas et al., 2016 ), which is the demethylase of H3K9me3 and is often highly expressed in BCa ( Kogure et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also suggest a high co-localization of activated STAT3 with SOX2+ cells in BCa. Another possible mechanism of Sox2 activation is epigenetic regulation; SOX2 can be activated by JMJD2A ( Bouzas et al., 2016 ), which is the demethylase of H3K9me3 and is often highly expressed in BCa ( Kogure et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic and molecular specification of each of these tissues is followed by morphogenetic events such as neural tube closure (NTC) and the epithelial to mesenchymal transition (EMT) of NC cells. Recent studies in chick, amphibian and mouse embryos have identified transcription factors that regulate ectodermal derivative fate specification (Buitrago-Delgado et al, 2015, Bouzas et al, 2016, Mach et al, 2016, Riddiford and Schlosser, 2016, Acloque et al, 2017, Simoes-Costa et al, 2015), NTC (Ray and Niswander, 2016a, Ray and Niswander, 2016b) and NC EMT (Rogers et al, 2013, Schiffmacher et al, 2014, Strobl-Mazzulla and Bronner, 2012). Comparative analysis of early transcriptional regulators shows that many have overlapping expression and directly or indirectly regulate the expression of specific adhesion molecules to control these processes (Ray and Niswander, 2016a, Fairchild et al, 2014, Fairchild and Gammill, 2013, Strobl-Mazzulla and Bronner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…KDM4A (also known as JMJD2A) is a demethylase that targets histone H3K9me2/3 and H3K36me2/3 leading to transcriptional activation. KDM4A has been shown to play an important role in gene expression [ 43 ], cellular differentiation [ 44 , 45 ] and cancer [ 46 ]. Tan et al .…”
Section: Introductionmentioning
confidence: 99%